Simultaneous EEG-fMRI for Functional Neurological Assessment - Mele, Giulia; Cavaliere, Carlo; Alfano, Vincenzo; Orsini, Mario; Salvatore, Marco; Aiello, Marco (Frontiers in Neurology, 2019)
The increasing incidence of neurodegenerative and psychiatric diseases requires increasingly sophis-ticated tools for their diagnosis and monitoring. Clinical assessment takes advantage of objective parameters extracted by electroencephalogram and magnetic resonance imaging among others, to support clinical management of neurological diseases. The complementarity of these two tools can be now emphasized by the possibility of integrating the two technologies in a hybrid solution, al-lowing simultaneous acquisition of the two signals by the novel EEG-fMRI technology. This review will focus on simultaneous EEG-fMRI technology and related early studies, dealing about issues related to the acquisition and processing of simultaneous signals, and including critical discussion about clinical and technological perspectives.